Stability assessment of crocetin and crocetin derivatives in Gardenia yellow pigment and Gardenia fruit pomace in presence of different cooking methods. (15th May 2020) - Li, Na; Fan, Mingcong; Li, Yan; Qian, Haifeng; Zhang, Hui; Qi, Xiguang; Wang, Li
Highlights: Seven crocetin derivatives (CDs) were identified by LC-MS and HPLC. Heating induced detachment of aglycon and the increase of trans/cis crocetin. Lighting induced oxidation and isomerization of CDs. Different cooking methods had distinct impacts on the stability of CDs. Steaming was able to retain the most content of CDs. Abstract: Gardenia fruit pomace (GFP) is a byproduct during the Gardenia oil production and rich in Gardenia yellow pigment (GY) in which the major functional components are crocetin and crocetin derivatives (CDs). The application of GFP was still limited. In this research, the stabilities of CDs during thermal and lighting treatment were studied, food systems with GY or GFP were simulated to evaluate the effects of cooking methods on CDs. Seven CDs were identified and determined in GY and GFP by UPLC-QToF-MS and HPLC. The stability results showed that CDs were sensitive to heat and light, the great loss of total CDs and detachment of aglycon were observed during thermal treatment. Light-driven degradation reactions of CDs fitted the first-order model. Different cooking methods (boiling, baking, steaming) had distinct impacts on the CDs contents in the simulated food system with GY and GFP, steaming should be an appropriate method for cooking.